From Pedagogy to Property: Copyright in Teaching Materials - Austin, Graeme W (Victoria University of Wellington Law Review, 2023)
Some university intellectual property policies claim the right to use some of the copyright-protected material that has been authored by academics. While the clauses in these policy instruments can vary in detail, the claim to use this material can extend to both traditional scholarly work, such as books and articles, together with teaching materials. This article considers whether the legal foundations for the claim are sound and whether the claim aligns with the characteristics of universities set out in the Education and Training Act 2020.